Rémission des symptômes de fibromyalgie : une étude phénoménologique-existentielle - Morin, Marie-Line (Canadian Journal of Counselling and Psychotherapy, 2007)
This article presents the case study of a 44-year-old woman who completely recovered from fibromyalgia symptoms through a psychological and spiritual growth journey. Using the existential phenomenological psychology research model, the meaning structure characterizing this journey is identified. On the basis of this structure, the author concludes the article by offering a theoretical reflection on the psychospiritual dimension of the subject, referring to the psychosynthesis concepts of "I" and the Transpersonal Self. These concepts are conceived as instances acting as a unifying centre in the personality and capable of playing a role in pacifying the unconscious conflict responsible for the psychosomatic disorder.